Rapid Method for Extraction of Genomic DNA FromVitex negundo L. - Sujin, R.M; De Britto, A.John; Mahesh, R; Dharmar, K. (Malaysian Journal of Science, 2010)
DNA extracted from plants which contains rich amount of polyphenols and or polysaccharides are often problematic when subjected when mature tissues are used for DNA extraction. In order to overcome these problems, we develope the first reliable and efficient method for isolating vitex negundo L. genomic DNA that is free from solubilising polysaccharides and polyphenols. This protocol uses NaCl, PVP, mercaptoethanol, SDS and incubation at 68Ã‚Â°C for 1 hour. Mild temperature conditions during extraction and precipitation were also recognized as important parameters. The quantity of isolated genomic DNA was confirmed by means of spectrophotometic analysis (260/280=1.6-1.8) routinely yielding 250-500 ng/l per gram of leaf material and it was proved through RAPD-PCR analysis.